ANALISIS PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Borolla, Johanis Darwin (PRESTASI, 2011)
This study aims to determine the effect of ownership structure that diproxykan by managerial ownership and institutional ownership on corporate value. Using a final sample 42 companies listed on Indonesian Stock Exchange in the period 2005-2009; take control of variable size and leverage , this study proves that the coefficient on institutional ownership variable is positive and statistically significant at 1% level, while managerial ownership is not getting the results significant. These results prove that the existence of institutions in corporate ownership structure will be an effective tool of management control so that the management can work well and ultimately firm value can be improved. Increasing managerial ownership has no impact on firm value.Keywords: managerial ownership, institutional, corporate value